LSAMP-NICE: Expanding International STEM Research for Underrepresented Minorities - Benjamin, Mary E.; Yates, Denise; Dupuis, Steve (Frontiers in Education, 2021)
Background: The global challenges of climate change, disease and hunger exceed national borders as do possibilities of sustained life, exploration and economic development in outer space. Both help to underscore the need for sustained international STEM research to leverage the talent embedded in different countries and in diverse groups within countries. This study focuses on the United States National Science Foundation provision of funds to its Louis Stokes Alliance for Minority Participation (LSAMP) Program to create a National Center of Excellence LSAMP-NICE for the establishment of international STEM Research Partnerships with a particular emphasis on the integration of international collaborative research for underrepresented minority STEM faculty, students and graduates. The study focuses on the diffusion of this Center’s services to the LSAMP Community, a group of 56 LSAMP funded STEM enrichment programs located across the United States. We found that LSAMP-NICE used mass media (a website and two advertorials in a national journal) and an annual national meeting as its major diffusion strategies during its first two years. Forty-two (42) programs responded to the questionnaire. The majority of the respondents (71.4%) had not used the website; 88.1% had not read the Advertorial in Science Magazine; and 78.6% did not attend the national 2019 LSAMP-NICE Annual Meeting in Washington, D.C. Our study suggests a need for additional diffusion techniques to reach the intended audience. Some respondent suggestions for diffusion include participation by LSAMP-NICE representatives at LSAMP Regional Conferences and Symposia, visits by LSAMP-NICE staff to LSAMP programs, forging relationships with higher education institutions abroad so LSAMP students can obtain summer or longer-term research experiences and providing technical assistance on applying for international travel funds.